The information content of forward moments - Andreou, Panayiotis; Kagkadis, Anastasios; Philip, Dennis; Taamouti, Abderrahim (My University, 2019)
We estimate the term structures of risk-neutral forward variance and skewness, and examine their predictive power for equity market excess returns and variance. We use Partial Least Squares to extract a single predictive factor from each term structure that is motivated by the theoretical implications of affine no-arbitrage models. The empirical analysis shows that an increased forward variance factor, FVF (forward skewness factor, FSF) corresponds to a more negatively sloped forward variance (more U-shaped forward skewness) term structure, and significantly forecasts higher future market excess returns and variance. More importantly, FSF exhibits predictive power for market returns that is stronger than, and incremental to, that provided by FVF. However, it does not outperform FVF in terms of excess variance predictability.
Keywords: Equity premium; Forward moments; Implied volatility surface; Partial least squares; Predictability of stock returns; Variance premium